TINJAUAN SOSIOLOGIS TENTANG PENTINGNYA AGAMA DALAM PERUBAHAN SOSIAL (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2017)
In fact, the phenomenon of social change illustrates and explains us that religion is one of the factors of social change itself. Religion became a basic format formation of the culture, how people live and thrive in the community. Religious teachings espoused, will characterize someone’s life in society, like or not, intentionally or unintentionally religious values had it could affect him in addressing the social changes occur. The question is whether religion that gives color to change or even religion becomes lost in the change.Studies in this article to make sense of how religious teaching can provide color in addressing current social changes that were increasingly more complex. A phenomenon that occurs writer temporary observation, religious teachings impressed being abandoned by the people with increased style and model of the changes that occur in people's lives can be widespread phenomenon JIL is factual enough to make Muslim unrest in this country. So through this paper is expected to eventually changes may have occurred, but the teachings of religion are upheld by its adherents as a driving force and source of ultimate truth and would be better serve as a filter against the change